The Investment Intention Among Indonesian Millennials via Peer-to-Peer Lending Applications - Poeteri, Nandike Ayudiah; Simanjuntak, Megawati; Hasanah, Nur (University of Merdeka Malang, 2021)
This study analyzes the factors influencing millennial investment intentions via Peer-to- Peer (P2P) lending applications through trust and perceived risk. This research was conducted by respondents who were selected using non-probability sampling, with the criteria that they had never used a P2P lending application and were born in 1982 to 2000. An online questionnaire gathered the data analysis using Structural Equation Modeling (SEM) with LISREL. The study results found that perceived reputation, perceived structural assurance, and trust had a significant effect on perceived risk. In contrast, financial literacy and perceived information quality are not. Next, relative advantage perceived reputation and perceived information quality significantly affect trust. Meanwhile, perceived structural assurance is not. Furthermore, perceived risk and trust have a significant effect on investment intention. However, perceived risk is more vital in mediating investment intention via P2P lending than trust. The organizers have discussed the managerial implications to consider increasing the number of potential investors, especially the millennial generation.JEL: G20, G41, O33